ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA DALAM MENGERJAKAN PEKERJAAN RUMAH MATEMATIKA SISWA MADRASAH ALIYAH AL-MUNAWWAROH MERAUKE TAHUN AKADEMIK 2017/2018 - Givanni Bulan Alfridha Saragih; Markus Palobo; Murni Sianturi (Musamus Journal of Mathematics Education, 2019)
This research is a quantitative descriptive research that aimed to discover the external factors affecting students in doing Mathematics Homework and to discover the most dominant external factors. The sample used in the research represented the entire population of sixty students. Data collecting techniques used is by distributing the questionnaires. The questionnaire contained nine external factors was tested for validity and reliability. Data analyzing technique used is descriptive analysis technique. The result of this research is nine external factors affecting the students of Madrasah Al-Munawwaroh in doing the Mathematics homework they are factor of follow up of the teacher in giving Mathematics homework as 97.5%, factor of giving the value of Mathematics homework as 98.33%, factor of type and nature of Mathematics homework as 81.67%, factor of responsibility and time to do the Mathematics homework as 85%, factor of the Mathematics homework difficulty level as 81.67%, factor of material and resources in doing Mathematics homework as 88.83%, factor of teaching method and Mathematics teacher characteristics as 90%, factor of friend influenced as 85%, and parents support as 72.5%. The dominant external factors are the factor of giving value in Mathematics homework, the factor of follow up of teachers in the giving Mathematics homework, and factor of how to teach and Mathematics teacher characteristic. Keywords: external factor; mathematic; homework.